Preliminary Evaluation of Clinical and Angiographic Outcomes with Biodegradable Polymer Coated Sirolimus-Eluting Stent in De Novo Coronary Artery Disease: Results of the MANIPAL-FLEX Study. (14th August 2016) - Shetty, Ranjan; Prajapati, Jayesh; Pai, Umesh; Shetty, Kiran
Abstract : Objective . The objective of the MANIPAL-FLEX study was to evaluate the feasibility, preliminary safety, and efficacy of the Supraflex sirolimus-eluting stent (SES) implantation, in de novo coronary artery disease, using clinical and quantitative coronary angiography (QCA) follow-ups. Methods . This was a prospective, nonrandomized, multicenter, single-arm study that enrolled 189 patients with de novo coronary artery disease who were treated with the Supraflex SES. Of 189 patients enrolled, the first 61 consecutive patients who consented to a 9-month follow-up evaluation by QCA, irrespective of presence of symptoms, were to be followed up with angiography at 9 months. The primary endpoint of the study was target lesion failure (TLF), including cardiac death, myocardial infarction, and target lesion revascularization during 12-month follow-up after the index procedure. Results . The mean age of the study population was58 ± 11 years, with 51.3% (97/189) of hypertensive patients. Total of 66 lesions, analyzed by offline QCA, showed good scaffolding of the target vessel with in-stent late lumen loss at 9 months of0.18 ± 0.23  mm. The observed TLF at 30-day, 6-month, and 12-month follow-up were 2 (1.1%), 6 (3.2%), and 10 (5.3%), respectively. Conclusion . This study provides preliminary evidence for the feasibility, safety, and efficacy of the Supraflex sirolimus-eluting stent.